A (Onto)Gênese da nação nas margens do território nacional: o projeto janarista territorial para o Amapá (1944-1956) - Silva, Maura Leal da (2007)
This work has as objective to study the foundation of the Território Federal do Amapá as purpose to the integration of this brazilian region nation and fundamentally to demonstrate that this political autonomy meant the conquest of a brazilian identity. How it was up to Janary Nunes as first territorial governor, the task of accomplishing this integration, in this way he became the Amapá imaginary founder . As central questions developed by this work, they have the images about Amazony as conditional element to the construction of the project which originated the amapaense territory; the administ>ration pretension of Janary Nunes in constructing a idea of the beginning to a new territory; the janarista administration base conditioned to the varguista ideals of development to the country; and the search in forming the amapaense brazilian citizen as fundamental element in the construction of the Amapá wondered. It was researched the files of the State produced during the Janary Nunes government (1944-1956) what it was used as sources: the newspapers of the territorial official press Amapá from this period; government reports; IBGE sources; official correspondence; Constituent Body Anals from 1946; books and memorials of this period